strategic Vigilance and their impact in Organizational success: Exploratory Research General AL-Faris company - محمود, زيد خوام (Journal of Economics and Administrative Sciences, 2017)
AbstractThe present search addressed the "strategic Vigilance and their impact in Organizational success "Where has the objective of strategic Vigilance and Organizational success of increasing importance at the present time, for being fairly modern topics, which have a tremendous impact on the success of organizations.                                                                                                       This research aims to find out what kinds of strategic watch available in General AL- Faris company, Ministry of industry, and the most important for the company, and learn the relationship and impact between vigilance strategy and organizational success, the system (SPSS) access to statistical results, General Knight company was chosen to the Ministry of industry as a research field study, and the study was composed of (Division Manager, Department head, Assistant General Manager, General Manager) (71) Personnel, formulated the hypothesis link the main contact between strategic Vigilance and Organizational success ramifications of which four hypotheses subsidiary, as formulated Four hypotheses influence between strategic Vigilance and Organizational success The ramifications of each of the four sub-hypotheses , the research found that all hypotheses link and influence between the variables and sub is a powerful and significant moral Research found that the best dimension of strategic vigilance is technology vigilance, and that all hypotheses link and effect between the primary and secondary variables are powerful and moral significance, as recommended by a number of recommendations, including: lack of focus on one type of company's strategic vigilance by administrative leaders, but diversification in using all kinds of vigilance (environmental, technology, trade and competitiveness), And at all administrative levels, with emphasis on environmental vigilance, because it means that the company's future by strengthening strengths and seize opportunities, work to recruit and orient new technologies towards the establishment of a network of communication and information between the various departments and divisions among and between its departments with support for communication and coordination among them